British and European Industrialization - Harley, CK (University of Oxford, 2013)
Modern economic growth – the simultaneous increase in population and average incomes – has been capitalism’s greatest achievement. This growth first became apparent in Britain in the nineteenth century and then spread to continental Europe (and the United States). The process is usually associated with the Industrial Revolution in Britain and the spread of British-type industrialization to follower economies. This chapter reviews the emergence of modern economic growth and suggests that the usual view is misleading in that it focuses is too limited both in time and in the technological change it usually emphasizes. On one hand, the of famous industries – textiles, iron and engineering – contributed only modestly to growth because they constituted only a small proportion of the economy. Furthermore, the emergence of growth was much more gradual than traditionally understood. In new views, Britain was already a substantially industrialized economy with relatively high wages before the early eighteenth century. The origin of growth appear to lie in the ability of an economy in which both product and factor markets were well developed in both the rural and urban areas to partially overcome Malthusian constraints. The spread of growth to continental Europe is often seen as the spread of new technology of the British Industrial Revolution. This too seems somewhat misleading. The industries were small relative to the entire economies and their success depended on particular conditions. Furthermore, just as Britain’s early success rested importantly on productive capitalist agriculture, the emergence of increased incomes on the continent depended on agricultural reforms that increases in its productivity.